Neuropsychological sequelae of aneurysmal sub-arachnoid haemorrhage in patients without neurological deficits 6 to 8 months post operatively : an exploratory study - Burbach, Frank Robert (Department of Psychology, 2016)
Bibliography: pages i-vii.